Implementación de un proceso de automatización en una caldera pirotubular, para controlar el sistema de calefacción de las piscinas, en la quinta recreacional pacific garden SOLDELOP CÍA. LTDA - Miranda Martínez, Elieser Natanael (2016)
With the Advancement of science and technology, everyday we find new projects and proposals, it is essential to upgrade academically and to strengthen the development of each areas of production, service and other activities in the revitalization for the economy of the countries. Pacific Garden is a leisure Center, that not have an automatic process to measure and control pool´s temperature; as a result, the elements involved in the process of heating electricity are consuming energy and fuel unnecessarily; because if the pool temperature reaches the level desired by the operator, it is not necessary that all machines continue working, otherwise they would be consuming electricity and fuel uncontrolled, and this involves waste money and time for the company. For this reason, It´s necessary to make the implementation of an automated process for heating swimming pools, It is performed by using a programmable logic controller and HMI screen, they are powerful tools that control industrial processes efficiently.